2016
DOI: 10.1007/s10909-016-1529-5
|View full text |Cite
|
Sign up to set email alerts
|

On the Dipole Moment of Quantized Vortices in the Presence of Flows

Abstract: The polarization charge  of an inhomogeneous superfluid system is expressed as a function of the order parameter 1 2 ( , )  r r . It is shown that if the order parameter changes on macroscopic distances, the polarization charge pol  is proportional to 2 A n  , and the polarization P is proportional to A n  , where n is the density of the system. For noninteracting atoms the proportionality coefficient A is independent of density, and in the presence of interaction A is proportional to n . The change of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…A variety of experimental and theoretical studies of dislocations in solid helium have revealed a number of their properties. One of the first theoretical predictions of the possibility of superfluidity along the cores of edge dislocations was that proposed by Shevchenko [52]. Recent experimental thermodynamic studies of solid helium (precise pressure measurements) [53] observed an additional pressure P ∼ T 2 contribution, which at T < 0.35 K exceeds the phonon contribution.…”
Section: Discussionmentioning
confidence: 97%
“…A variety of experimental and theoretical studies of dislocations in solid helium have revealed a number of their properties. One of the first theoretical predictions of the possibility of superfluidity along the cores of edge dislocations was that proposed by Shevchenko [52]. Recent experimental thermodynamic studies of solid helium (precise pressure measurements) [53] observed an additional pressure P ∼ T 2 contribution, which at T < 0.35 K exceeds the phonon contribution.…”
Section: Discussionmentioning
confidence: 97%
“…In solid 4 He, dislocations are extremely mobile and can reduce the solid's shear modulus by as much as 90%-an effect referred to as "giant plasticity" [10]. It has been proposed that some dislocations in 4 He have superfluid cores [11,12] which would allow new phenomena like "giant isochoric compressibility" [12], "superclimb" [13], and superflow in the dislocation network [11,14]. However, the most important open question involves mass flow.…”
mentioning
confidence: 99%
“…The superfluid contribution would dominate because, experimentally, it is seen that limitation of dislocation motion in conventional crystals due to Peierls barrier is absent in solid 4 He. The onset temperature of this unusual elastic behavior in solid 4 He is in the same temperature range as the onset of superfluid behavior in [50,18] dislocation networks. As noted above, the superfluid contribution to dislocation mobility scales with the superfluid fraction i.e.…”
Section: Discussionmentioning
confidence: 71%
“…According to Refs. [50,18] dislocation network superfluidity is characterized by two temperature scales -T 0 ∼ 1K (comparable to the bulk λ temperature for liquid 4 He) and T c ∼ T 0 a/L f , where a is the interatomic distance along a dislocation core and L f is the free segment length of dislocation line. Within such a model for superfluidity associated with dislocation lines, the onset temperatures are roughly consistent with the experimentally [11,51,52] found range 0.1K to 0.075K where the onset of anomalous behavior is observed.…”
Section: Results -Modeling Of Experimental Shear Modulus Datamentioning
confidence: 99%